2019
DOI: 10.1080/21655979.2019.1621136
|View full text |Cite
|
Sign up to set email alerts
|

sCLU as prognostic biomarker and therapeutic target in osteosarcoma

Abstract: Osteosarcoma (OS) is the most common primary malignant bone tumor. Secretory apolipoprotein J/clusterin (sCLU) is overexpressed in many cancers; however, its role in OS has not been previously investigated. The objectives of this study were to address this question and also to assess the clinical value of sCLU as a prognostic biomarker and therapeutic target by comparing sCLU expression in human OS (n = 106), normal bone (n = 16), fibrous dysplasia (n = 9), and ossifying myositis (n = 11) tissues and by evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…This may be due to the following aspects: The increased expression levels of sCLU may directly translate to elevated drug resistance, and sCLU may influence the expression of certain other genes and may be associated with the response to other drugs. For instance, various other studies have reported that sCLU was associated with drug resistance of osteosarcoma cells [11] and prostate cancer cells [40]. Furthermore, the increased resistance to drugs was not entirely due to the elevation of sCLU, and is probably regulated by additional signaling pathways, including the activating AKT/GSK3β/β-catenin axis [41] and Wnt/β-catenin and IGF-I signaling [40].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This may be due to the following aspects: The increased expression levels of sCLU may directly translate to elevated drug resistance, and sCLU may influence the expression of certain other genes and may be associated with the response to other drugs. For instance, various other studies have reported that sCLU was associated with drug resistance of osteosarcoma cells [11] and prostate cancer cells [40]. Furthermore, the increased resistance to drugs was not entirely due to the elevation of sCLU, and is probably regulated by additional signaling pathways, including the activating AKT/GSK3β/β-catenin axis [41] and Wnt/β-catenin and IGF-I signaling [40].…”
Section: Discussionmentioning
confidence: 98%
“…sCLU is found to be overexpressed in osteosarcoma (OS), and sCLU overexpression is associated with metastasis and chemoresistance. Furthermore, targeting sCLU inhibits metastasis and enhances chemosensitivity in OS cells [11]. Aberrant sCLU expression is involved in a number of molecular pathways related to the mechanisms of chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated to physically bind to the taxane drug paclitaxel in ovarian cancer cells, potentially limiting its activity [42]. Exogenously applied clusterin has also been shown to inhibit taxane-mediated microtubule stabilisation, enhance ERK-mediated survival signalling, and promote mitotic progression by inhibiting Cdc25C kinase to limit the action of mitosis-targeting agents [42][43][44][45]. It is unclear whether extracellular clusterin translocates into cells to achieve these effects.…”
Section: Nonenzymatic Proteinsmentioning
confidence: 99%
“…CLU was indicated to be elevated in several tumor types. CLU confers chemoresistance to numerous cancer types, including primary breast cancer ( 37 ), pancreatic cancer ( 38 ), lung cancer ( 39 ), osteosarcoma ( 40 ) and prostate cancer ( 41 ). Accordingly, custirsen, a second-generation antisense oligonucleotide, was designed to inhibit the expression of CLU.…”
Section: Discussionmentioning
confidence: 99%